Polarizabilities of Rn-like Th4+ from rf spectroscopy of Th3+ Rydberg levels - Keele, Julie A.; Lundeen, S. R.; Fehrenbach, C. W. (My University, 2011)
High-resolution studies of the fine-structure pattern in high-L n = 37 levels of Th3+ have been carried out using radio-frequency (rf) spectroscopy detected with resonant excitation Stark ionization spectroscopy (RESIS). Intervals separating L = 9 to L = 15 levels have been measured, and the results analyzed with the long-range effective potential model. The dipole polarizability of Th4+is determined to be αD = 7.720(7) a.u. The quadrupole polarizability is found to be 21.5(3.9) a.u. Both measurements represent significant tests of a priori theoretical descriptions of this highly relativistic ion.